Respuesta :

Answer:

(33,-260)

Step-by-step explanation:

y=2(3)².....equation(1)

y=2/3x -4 ...equation(2)

put equation(1) to equation(2)

2(3)² = 2/3x - 4

2(9)= 2/3x - 4

18 = 2/3x - 4

add 4 to both sides

18+4 = 2/3 x- 4 +4

22 = 2/3x

multiply via by 3

22×3 = 2/3x × 3

66 = 2x

divide both sides by 2

66/2 = 2x/2

33 = x

x=33

solve for y

to solve for y, put x in equation (2)

y=2/3x - 4

y = 2/3(33) - 4

y = 2/66 - 4

find the LCM of 66 and 1

the LCM is 66

multiply by their LCM

y = (2/66)66-4×66

y = 2 - 264

y = -260

solution= (33,-260)